2007
DOI: 10.1007/s11858-007-0065-9
|View full text |Cite
|
Sign up to set email alerts
|

The role of examples in forming and refuting generalizations

Abstract: Acknowledging students' difficulty in generalizing in general and expressing generality in particular, we assert that the choice of examples that learners are exposed to plays a crucial role in developing their ability to generalize. We share with the readers experiences in which examples supported generalization, and elucidate the strategies that worked for us in these circumstances, presuming that similar strategies could be helpful with other students in other settings. We further share several pitfalls and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
7

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 18 publications
0
23
0
7
Order By: Relevance
“…Van Dormolen & Zaslavsky, 2003), students' beliefs about them (Zaslavsky & Shir, 2005), and students' guided collaborative development of definitions in contexts new to them (Larsen & Zandieh, 2008;Zandieh & Rasmussen, 2010). Studies have suggested that students who spontaneously generate examples in response to new definitions later perform better on tasks involving the defined concepts (Dahlberg & Housman, 1997), and there has been much recent discussion of the way in which example generation tasks might help students to modify their example spaces so that these more closely coincide with the extensions of the defined concepts (Mason, 2002;Watson & Mason, 2005;Zazkis, Liljedahl & Chernoff, 2008;Zazkis & Leikin, 2008). Definitions are also discussed in the extensive literature on proof, which focuses on the role of definitions as a deductive base in arguments about whole classes of objects.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Van Dormolen & Zaslavsky, 2003), students' beliefs about them (Zaslavsky & Shir, 2005), and students' guided collaborative development of definitions in contexts new to them (Larsen & Zandieh, 2008;Zandieh & Rasmussen, 2010). Studies have suggested that students who spontaneously generate examples in response to new definitions later perform better on tasks involving the defined concepts (Dahlberg & Housman, 1997), and there has been much recent discussion of the way in which example generation tasks might help students to modify their example spaces so that these more closely coincide with the extensions of the defined concepts (Mason, 2002;Watson & Mason, 2005;Zazkis, Liljedahl & Chernoff, 2008;Zazkis & Leikin, 2008). Definitions are also discussed in the extensive literature on proof, which focuses on the role of definitions as a deductive base in arguments about whole classes of objects.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Another of the ZDM papers that does not focus on sequential examples is by Zazkis, Liljedahl and Chernoff (2008). Their interest is in the role of examples, and they argue that 'the choice of examples that learners are exposed to plays a crucial role in developing their ability to generalize' (p. 131).…”
Section: The Foregrounding Of a Number-pattern-spotting Approach In Cmentioning
confidence: 99%
“…Students are able to see the structure of the pattern based on consecutive terms and found it easier to state the relationship verbally than algebraically (e.g. Zazkis et al 2008). Lastly, students' uses of representations to make generalisations also might cause some difficulties.…”
Section: Generalising Number Patternsmentioning
confidence: 99%